Dentists’ decisions on prophylactic removal of mandibular third molars: a 10-year follow-up study - Knutsson K, Lysell L, Rohlin M (Blackwell Synergy, 2001)
In recent years, several critical outcome studies concerning the prophylactic removal of mandibular third molars have been published. These would appear to motivate a more restrictive approach today as compared with 10 years ago. The aim of the present study was to examine dentists’ decisions on the prophylactic removal of impacted mandibular third molars over a 10-year period